Mu opioid modulation of oxytocin secretion in late pregnant and parturient rats - Involvement of noradrenergic neurotransmission - Kutlu, S; Yilmaz, B; Canpolat, S; Sandal, S; Ozcan, M; Kumru, S; Kelestimur, H (Karger, 2004)
We have investigated effects of mu- and kappa-opioid agonists and antagonists on plasma oxytocin levels and noradrenaline content in the supraoptic nucleus ( SON) and paraventricular nucleus (PVN) of 20-day pregnant rats. beta-Endorphin, oxytocin, estrogen and progesterone profiles in late pregnant and parturient rats were also sought. Stage of estrous cycle was monitored by vaginal smear, and pro-estrous animals were left overnight with male. In the first set of experiments, pregnant rats were monitored and decapitated on days 20 and 21 and after the delivery of second pup. In the second set, 20-day pregnant rats were intracerebroventricularly infused with morphine (50 mug/10 mul), U50,488H (kappa-agonist; 50 mug/10 mul), clocinnamox (mu-antagonist; 50 mug/10 mul) and norbinaltorphimine (kappa-antagonist; 50 mug/10 mul). Controls received saline alone. Serum estrogen and progesterone levels were measured by enzyme immunoassay, and plasma oxytocin and beta-endorphin by radioimmunoassay. Noradrenaline and its metabolite (3,4-dihydroxyphenylglycol) were determined in micropunched hypothalamic nuclei by HPLC-ECD. In parturient rats, oxytocin levels were increased (p < 0.05) and beta-endorphin decreased (p < 0.01) compared to 20-day pregnant animals. Serum progesterone concentrations progressively declined towards parturition (p < 0.001). Clocinnamox raised oxytocin levels (p < 0.01) while U50,488H caused decreases (p < 0.05). Noradrenaline content was elevated by clocinnamox in the SON (p < 0.01) and PVN (p < 0.05) compared to control values. Other agonists and antagonists had no significant effect on the noradrenergic neurotransmission or oxytocin secretion. We suggest that noradrenaline may mediate the inhibitory effects of mu-opioids on oxytocin release. Our findings have also shown that kappa-opioid receptors are not involved in modulation of oxytocin neurons in late pregnant rats. Copyright (C) 2004 S. Karger AG, Basel.
Keywords: opioid peptides; vasopressin; oxytocin; catecholamine; opioid antagonists; endorphins; gonadal steroids; noradrenaline